Level and determinants of infant and under-five mortality in Wad-Medani Town, Sudan - Huda M Haroun; Mohmamed S Mahfouz; Khalid H Ibrahim (Wolters Kluwer Medknow Publications, 2007)
Aim: This study aimed to determine the level of infant and under-five mortality rates and to examine the effect of socioeconomic, demographic and environmental factors on the health status of the children under five years. Methods: The data for this study were collected by means of a questionnaire addressed to women in Wad-Medani, Sudan. Three hundred women in the reproductive age (15-49) years were chosen randomly for this study. The data were analyzed statistically using the Statistical Package for Social Sciences (SPSS). Frequency distributions and a statistical test based on Chi-square for independence was conducted. Results: Infant mortality rate was 77 per 100 and child mortality rate was 67 per 100. The results revealed that immunization, child order, child birth weight, birth interval and contraceptive use had a significant influence on the mortality of children under the age of five. The mother's level of education is highly significant on the mortality of children under five years old. Conclusions: The Ministry of Health should give greater attention to improving immunization services and concentrate on health education campaigns for mothers and for the community.